Preparation of Reduced Graphene Oxide (RGO) Modified Titanium Dioxide Nanotube (TNTs) as Visible Light Effective Catalyst for the Conversion of CO2 to CH4 - Khatun, Fatema; Azrina, Abd Aziz; L. C., Sim (IOP Publishing, 2020)
In this study, a modified visible light active photocatalyst has been prepared where titanium dioxide nanotube (TNTs) was coupled with reduced graphene oxide (RGO) through a facile synthesis process. The photoactivity of the RGO-TNTs has been evaluated by converting CO2 to CH4 under visible light irradiation. In order to justify the photo-effectivity of the catalysts, physical and optical characterization were performed through FESEM, EDX, UV-Vis absorption spectra and PL spectra. The morphological analysis shows homogeneous RGO distribution on the TiO2 nanotube whereas elemental compositional analysis revealed the presence of all elements in the prepared catalyst. Visible light enhancement activity of the prepared catalyst after the incorporation of RGO was exposed by UV-Vis analysis due to its enhanced light absorption properties. Improved electron-hole separation rate was investigated for the RGO incorporated TNTs through PL analysis. The fruitful incorporation of the RGO with TNTs further affirmed by the increased photocatalytic activity by converting CO2 to CH4 that acquired enhanced CH4 production (9.27%) which is 1.81 times higher than the CH4 production rate obtained through TNTs (5.12%). Thus, this study induces a simple synthesis procedure to modify TNTs as a visible light active photocatalyst with the integration of RGO. Moreover, RGO-TNTs enhanced visible light activity were evaluated through the conversion of CO2 to CH4.